Research on Mathematical Resilience: A Literature Review - Azka Rabbihadi Joe; Meiliasari Meiliasari; Wardani Rahayu (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
This systematic review has the objective to define the concept and to analyze the empirical studies of mathematical resilience through the following procedures: 1) developing a research question; 2) defining selection criteria; 3) developing the search strategy; 4) study selection process; 5) appraising the quality of studies; and 6) synthesis result. 19 articles were selected and reviewed in total. This study shown the concept representation and also insight of empirical studies about mathematical resilience.